Pengaruh Pendidikan Kesehatan Dengan Metode Simulasi Pertolongan Pertama (Management Airway) Pada Penyintas Dengan Masalah Sumbatan Jalan Nafas pada Masyarakat Awam di Kec.Sawit Kab. Boyolali - Akhmad Rifai; Sugiyarto Sugiyarto ((JKG) Jurnal Keperawatan Global, 2019)
Background: Airway management is the most important thing in resuscitation and requires special skills in the management of emergencies, therefore the first thing that must be assessed is the smoothness of the airway, which includes airway examinations that can be caused by foreign bodies. The lack of oxygen is a cause of rapid death. Research Objectives The general objective of this research is to improve the ability of airway management skills ordinary people in Kateguhan, Sawit, Boyolali. Methods: This research is an experimental study with a Pre-Test-Post Test one Group control design approach. through testing research hypotheses. The population of this research is the cloud community of 50 respondents which are divided into two groups, 25 respondents in the intervention group and 25 respondents as a control group. Statistical test in the paired group uses the nonparametric Wilcoxon test and the non-paired uses Mann-Whitney. Results: Based on the results of the Wilcoxon analysis test it can be concluded that the 25 respondents who conducted training in simulation measures by way of air way management training specifically airway obstruction can be drawn the conclusion that the majority of ordinary people have good knowledge in terms of emergency handling abilities, especially in air way management measures p value 0.001 which means that there are significant differences between before and after training. In the control group there were also significant differences with a P value of 0.001. Based on the Mann-Whitney test analysis, there were significant differences between the intervention and control groups with a p value of 0.001. Conclusion: Airway management education and training courses for lay people continue to be held to improve the ability of the action skills.